Can geocaching be an indicator of cultural ecosystem services? The case of the montado savannah-like landscape - do Rosario, Ines T.; Rebelo, Rui; Cardoso, Paulo; Segurado, Pedro; Mendes, Ricardo N.; Santos-Reis, Margarida (Ecological Indicators, 2019)
Cultural Ecosystem Services (CES) are difficult to assess and are seldom considered by land managers. Geocaching, an outdoor game that uses Global Positioning System (GPS) enabled devices to find hidden containers (geocaches) in certain locations, has been seldom used as a data source to assess CES. However, contrary to other crowdsourcing databases, geocaching allows to associate particular experiences to accurate locations. Furthermore, databases generated by geocachers provide an ideal case to compare revealed preferences (the frequency of visits to a specific geocache) with stated preferences (a posteriori evaluation of each location). We tested the relevance of geocaching databases as CES indicators using a dataset of 50 818 geocaches spread across continental Portugal, over eight land-use classes, with a focus on the montado (a high nature value farmland found in Southwestern Iberian Peninsula). We found that site visitation frequency was related with its availability, showing no revealed preference towards any land use. However, site evaluations by geocachers, measured either through the number of words describing the experience, the number of photos taken, or the number of votes for “favourite geocaches”, showed marked differences in their stated preferences, with higher appreciation for open land uses in general, and montado in particular, especially when compared to other forested landscapes. Our results may contribute to the design of regional development and land-use management policies of this threatened landscape, since they show the system’s strong potential as CES provider and, consequently, promoter of diversification of activities.
Keywords: Crowdsourcing databases; iberian peninsula; land use; spatial analysis; Stated and revealed preferences

Biomass-modulated fire dynamics during the last glacial-interglacial transition at the Central Pyrenees (Spain) - Gil-Romera, Graciela; González-Sampériz, Penélope; Lasheras-Álvarez, Laura; Sevilla-Callejo, Miguel; Moreno, Ana; Valero-Garcés, Blas; López-Merino, Lourdes; Carrión, José S; Pérez Sanz, Ana; Aranbarri, Josu; García-Prieto Fronce, Eduardo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2014)
Understanding long-term fire ecology is essential for current day interpretation of ecosystem fire responses. However palaeoecology of fire is still poorly understood, especially at high-altitude mountain environments, despite the fact that these are fire-sensitive ecosystems and their resilience might be affected by changing fire regimes. We reconstruct wildfire occurrence since the Lateglacial (14.7calka BP) to the Mid-Holocene (6calka BP) and investigate the climate–fuel–fire relationships in a sedimentary sequence located at the treeline in the Central Spanish Pyrenees. Pollen, macro- and micro-charcoal were analysed for the identification of fire events (FE) in order to detect vegetation post-fire response and to define biomass–fire interactions. mean fire intervals (mfi) reduced since the Lateglacial, peaking at 9–7.7calka BP while from 7.7 to 6calka BP no fire is recorded. We hypothesise that Early Holocene maximum summer insolation, as climate forcing, and mesophyte forest expansion, as a fuel-creating factor, were responsible for accelerating fire occurrence in the Central Pyrenees treeline. We also found that fire had long-lasting negative effects on most of the treeline plant communities and that forest contraction from 7.7calka BP is likely linked to the ecosystem's threshold response to high fire frequencies.
Keywords: Fire history; historical biogeography; iberian peninsula; l Palaeoecology; Lateglacia; quaternary

Predicting the natural vegetation in a region by comparing the pollen in two biological vectors: bryophytes and honey - González-Porto, A V; Martín-Arroyo, T (Grana, 2013)
The range of pollen that can be found around the city of Sigüenza has been analysed (La Alcarria, north-eastern region, Guadalajara, Spain), an area currently included in the territory comprising the Protected Origin Denomination ‘Miel de la Alcarria’. We studied the pollen recovered from two different types of biological sensors: bryophytes, live material used to study the recent pollen rain, and honey. The aim of this study was to try to establish the relationship between the pollen collected from both types of sensors and the existing natural vegetation in the area using comparative statistical methods. More than 7500 pollen grains were observed from the bryophyte samples and included 35 pollen types. Conversely, the pollen present in 37 honey samples contained 46 pollen types with a total of 46 000 pollen grains counted. The data presented in this study proves the relationship between the bryophyte pollen spectrum and the local vegetation present in a geographical area. However, it indicates that the pollen content in honey is a more effective measurement to determine spatial distribution of the plant species.We conclude that the pollen present in honey may better predict the vegetation in a region than that recovered from bryophytes.
Keywords: Apis mellifera; bryophytes layer; Guadalajara; iberian peninsula; landscape plant; surface pollen sample; Vegetation

Volatile organic compounds in the western Mediterranean basin: urban and rural winter measurements during the DAURE campaign - Seco, R; Penuelas, J; Filella, I; Llusia, J; Schallhart, S; Metzger, A; Mueller, M; Hansel, A (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2013)
Atmospheric volatile organic compounds (VOCs) have key environmental and biological roles, but little is known about the daily VOC mixing ratios in Mediterranean urban and natural environments. We measured VOC mixing ratios concurrently at an urban and a rural site during the winter DAURE campaign in the northeastern Iberian Peninsula, by means of PTR-MS at both locations: a PTR-Quad-MS at the urban site and a PTR-ToF-MS at the rural site. All VOC mixing ratios measured were higher at the urban site (e. g. acetaldehyde, isoprene, benzene, and toluene with averages up to 1.68, 0.31, 0.58 and 2.71 ppbv, respectively), with the exception of some short-chain oxygenated VOCs such as acetone (with similar averages of 0.7-1.6 ppbv at both sites). The average diurnal pattern also differed between the sites. Most of the VOCs at the urban location showed their highest mixing ratios in the morning and evening. These peaks coincided with traffic during rush hour, the main origin of most of the VOCs analyzed. Between these two peaks, the sea breeze transported the urban air inland, thus helping to lower the VOC loading at the urban site. At the rural site, most of the measured VOCs were advected by the midday sea breeze, yielding the highest daily VOC mixing ratios (e. g. acetaldehyde, isoprene, benzene, and toluene with averages up to 0.65, 0.07, 0.19, and 0.41 ppbv, respectively). Only biogenic monoterpenes showed a clear local origin at this site. In addition, the concentrations of fine particulate matter observed at both sites, together with the synoptic meteorological conditions and radio-sounding data, allowed the identification of different atmospheric scenarios that had a clear influence on the measured VOC mixing ratios. These results highlight the differences and relationships in VOC mixing ratios between nearby urban and rural areas in Mediterranean regions. Further research in other urban-rural areas is warranted to better understand the urban-rural influence on atmospheric VOC mixing ratios under different atmospheric conditions.
APS
Keywords: iberian peninsula; Mediterranean; Monoterpenes; VOCs

Factors driving growth responses to drought in Mediterranean forests - Pasho, Edmond; Camarero, J Julio; Luis, Martín; Vicente-Serrano, Sergio M (European Journal of Forest Research, 2012)
We lack information regarding the main factors driving growth responses to drought in tree species with different vulnerability against this stressor and considering sites with contrasting climatic conditions. In this paper, we identify the main drivers controlling growth response to a multi-scalar drought index (Standardized Precipitation Index, SPI) in eight tree species (Abies alba, Pinus halepensis, Quercus faginea, Pinus sylvestris, Quercus ilex, Pinus pinea, Pinus nigra, Juniperus thurifera). We sampled forests growing across a pronounced climatic gradient under Mediterranean conditions in north-eastern Spain. To summarize the patterns of growth responses to drought, we used principal component analysis (PCA). To determine the main factors affecting growth responses to drought, correlation and regression analyses were carried out using a set of abiotic (climate, topography, soil type) and biotic (Normalized Difference Vegetation Index, Enhanced Vegetation Index, tree-ring width, diameter at breast height) predictors and the PCs loadings as response variables. The PCA analysis detected two patterns of growth responses to drought corresponding to xeric and mesic sites, respectively. The regression analyses indicated that growth responses to drought in xeric forests were mainly driven by the annual precipitation, while in mesic sites the annual water balance was the most important driver. The management of Mediterranean forests under the forecasted warmer and drier conditions should focus on the main local factors modulating the negative impacts of drought on tree growth in xeric and mesic sites.
Keywords: Dendrochronology; Drought; iberian peninsula; Radial growth; Standardized precipitation index

Holocene changes in precipitation seasonality in the western Mediterranean Basin: a multi-species approach using δ13C of archaeobotanical remains - Aguilera, M.; Ferrio, J. P.; Pérez, G.; Araus, J. L.; Voltas, J. (Journal of Quaternary Science, 2012)
Precipitation has been of utmost importance in shaping the evolution of landscapes and human settlements in the Mediterranean. However, information on seasonal precipitation patterns through the Holocene is scarce. This study attempts to quantify the evolution of seasonal precipitation in the East Iberian Peninsula (5000 BC to AD 600) based on the carbon isotope composition (δ13C) of archaeobotanical remains. Data on Holm oak, Aleppo pine and small-grain cereals were combined, and precipitation was inferred from models relating present-day records to the δ13C of modern samples. Subsequently, charred grains were used as a proxy for ancient moisture during April–May, whereas oak and pine charcoals provided complementary rainfall estimates for September–December and January–August, respectively. The results reveal aridity changes throughout the Holocene in the western Mediterranean. Past spring–summer precipitation was consistently higher than at present. In contrast, autumn and early winter precipitation showed stronger fluctuations, particularly during the first millennium BC, and often exhibited values below those of the present. The high contribution of autumn precipitation to the annual water budget, typical of the present Mediterranean climate, was definitively established at the beginning of the current era. This study shows how a combination of species holding complementary environmental signals can contribute to a wider knowledge of local precipitation dynamics. Copyright © 2011 John Wiley & Sons, Ltd.
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Ltd.
Keywords: carbon isotopes; charred grains; iberian peninsula; Pinus halepensis; Quercus ilex

Implementation of a module for risk of ozone impacts assessment to vegetation in the Integrated Assessment Modelling system for the Iberian Peninsula. Evaluation for wheat and Holm oak. - de Andrés, Juan Manuel; Borge, Rafael; de la Paz, David; Lumbreras, Julio; Rodríguez, Encarnación (Environmental pollution (Barking, Essex : 1987), 2012)
A module to estimate risks of ozone damage to vegetation has been implemented in the Integrated Assessment Modelling system for the Iberian Peninsula. It was applied to compute three different indexes for wheat and Holm oak; daylight AOT40 (cumulative ozone concentration over 40 ppb), cumulative ozone exposure index according to the Directive 2008/50/EC (AOT40-D) and POD(Y) (Phytotoxic Ozone Dose over a given threshold of Y nmol m(-2) s(-1)). The use of these indexes led to remarkable differences in spatial patterns of relative ozone risks on vegetation. Ozone critical levels were exceeded in most of the modelling domain and soil moisture content was found to have a significant impact on the results. According to the outputs of the model, daylight AOT40 constitutes a more conservative index than the AOT40-D. Additionally, flux-based estimations indicate high risk areas in Portugal for both wheat and Holm oak that are not identified by AOT-based methods.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 22398018
Keywords: Air Pollutants; Air Pollutants: analysis; Air Pollutants: toxicity; Chemical; CMAQ WRF; Critical level; Environmental Monitoring; Environmental Monitoring: methods; iberian peninsula; Models; Ozone; Ozone risk assessment; Ozone: analysis; Ozone: toxicity; Portugal; Quercus; Quercus: drug effects; Quercus: growth & development; Risk Assessment; Stomatal conductance; Triticum; Triticum: drug effects; Triticum: growth & development

Disentangling the relative importance of climate, size and competition on tree growth in Iberian forests: implications for forest management under global change - Gómez-Aparicio, LORENA; GARCÍA-VALDÉS, Raúl; Ruíz-Benito, PALOMA; Zavala, MIGUEL a (Global Change Biology, 2011)
Most large-scale multispecies studies of tree growth have been conducted in tropical and cool temperate forests, whereas Mediterranean water-limited ecosystems have received much less attention. This limits our understanding of how growth of coexisting tree species varies along environmental gradients in these forests, and the implications for species interactions and community assembly under current and future climatic conditions. Here, we quantify the absolute effect and relative importance of climate, tree size and competition as determinants of tree growth patterns in Iberian forests, and explore interspecific differences in the two components of competitive ability (competitive response and effect) along climatic and size gradients. Spatially explicit neighborhood models were developed to predict tree growth for the 15 most abundant Iberian tree species using permanent-plot data from the Spanish Second and Third National Forest Inventory (IFN). Our neighborhood analyses showed a climatic and size effect on tree growth, but also revealed that competition from neighbors has a comparatively much larger impact on growth in Iberian forests. Moreover, the sensitivity to competition (i.e. competitive response) of target trees varied markedly along climatic gradients causing significant rank reversals in species performance, particularly under xeric conditions. We also found compelling evidence for strong species-specific competitive effects in these forests. Altogether, these results constitute critical new information which not only furthers our understanding of important theoretical questions about the assembly of Mediterranean forests, but will also be of help in developing new guidelines for adapting forests in this climatic boundary to global change. If we consider the climatic gradients of this study as a surrogate for future climatic conditions, then we should expect absolute growth rates to decrease and sensitivity to competition to increase in most forests of the Iberian Peninsula (in all but the northern Atlantic forests), making these management considerations even more important in the future.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 2 march 2011; climate change; competitive effect; competitive response; Forests; iberian peninsula; march 2011 and accepted; maximum likelihood; Mediterranean; Mediterranean forests; neighhorbood models; received 21 october 2010; revised version received 1; species rank reversals; tree coexistence

Effects of a low severity prescribed fire on water-soluble elements in ash from a cork oak (Quercus suber) forest located in the northeast of the Iberian Peninsula. - Pereira, Paulo; Úbeda, Xavier; Martin, Deborah; Mataix-Solera, Jorge; Guerrero, César (Environmental research, 2011)
Wildfire is the major disturbance in Mediterranean forests. Prescribed fire can be an alternative to reduce the amount of fuel and hence decrease the wildfire risk. However the effects of prescribed fire must be studied, especially on ash properties, because ash is an important nutrient source for ecosystem recovery. The aim of this study is to determine the effects of a low severity prescribed fire on water-soluble elements in ash including pH, electrical conductivity (EC), calcium (Ca), magnesium (Mg), sodium (Na), potassium (K), aluminum (Al), manganese (Mn), iron (Fe), zinc (Zn), silica (SiO(2)) and total sulphur (TS). A prescribed fire was conducted in a cork oak (Quercus suber) (Q.S) forest located in the northeast part of the Iberian Peninsula. Samples were collected from a flat plot of 40×70m mainly composed of Q.S and Quercus robur (Q.R) trees. In order to understand the effects of the prescribed fire on the soluble elements in ash, we conducted our data analysis on three data groups: all samples, only Q.S samples and only Q.R samples. All three sample groups exhibited a significant increase in pH, EC (p<0.001), water-soluble Ca, Mg, Na, SiO(2) and TS and a decrease in water-soluble Mn, Fe and Zn. Differences were identified between oak species for water-soluble K, Al and Fe. In Q.S samples we registered a significant increase in the first two elements p<0.001 and p<0.01, respectively, and a non-significant impact in the third, at p<0.05. In Q.R data we identified a non-significant impact on water-soluble K and Al and a significant decrease in water-soluble Fe (p<0.05). These differences are probably due to vegetation characteristics and burn severity. The fire induced a higher variability in the ash soluble elements, especially in Q.S samples, that at some points burned with higher severity. The increase of pH, EC, Ca, Mg, Na and K will improve soil fertility, mainly in the study area where soils are acidic. The application of this low severity prescribed fire will improve soil nutrient status without causing soil degradation and thus is considered to be a good management strategy.
Keywords: Ash; iberian peninsula; Prescribed fire; Quercus robur; Quercus suber

Occurrence of Reticulitermes grassei (Isoptera: Rhinotermitidae) on Cork Oaks in the Southern Iberian Peninsula: Identification, Description and Incidence of the Damage - Gallardo, Patricia; Cardenas, Ana M.; Gaju, Miguel (SOCIOBIOLOGY, 2010)
This paper describes a new type of damage that affects cork oaks (Quercus suber L.) in the south of the Iberian Peninsula. The shape of the damage suggests that it could be caused by termites. The main aim of this research was to identify the causal agent of the damage, to describe it and to assess its presence and incidence in the area. Several field experiments were carried out in which specific baited-traps for termites were used. At the end of the sampling period, termites (identified as Reticulitermes c.f.grassei Clement) were found in most of the traps located under damaged trees. Descriptions related to the appearance, form and sizes of the galleries made by the termites are provided, as well as data on the infestation level and damage intensity. Differences with damage caused by other woodborer insects are also discussed.
The following values have no corresponding Zotero field: pub-location: DEPT BIOL SCI, CHICO, CA 95929 USA publisher: CALIFORNIA STATE UNIV
Keywords: cork damage; iberian peninsula; Quercus suber; Reticulitermes grassei; Rhinotermitidae

Epigeous macrofungi of the Parque de Natureza de Noudar in Alentejo (Portugal) - Louro, R.; Calado, M.; Pinto, B.; Santos-Silva, C. (Mycotaxon, 2009)
This inventory represents the first list of the epigeous macrofungi collected in Parque de Natureza de Noudar (Barrancos, Alentejo, Portugal). Throughout 3 years 162 taxa were registered, from which 8 are new species for Portugal and 77 for Alentejo. Some of them are considered rare species whereas others have been suggested to acquire a conservation status.
Keywords: fungi; Holm oak; iberian peninsula; Mediterranean ecosystem; sporocarps

Epigeous macrofungi of the Parque de Natureza de Noudar in Alentejo (Portugal) - Louro, R; Calado, M; Pinto, B; Santos-Silva, C (Mycotaxon, 2009)
This inventory represents the first list of the epigeous macrofungi collected in Parque de Natureza de Noudar (Barrancos, Alentejo, Portugal). Throughout 3 years 162 taxa were registered, from which 8 are new species for Portugal and 77 for Alentejo. Some of them are considered rare species whereas others have been suggested to acquire a conservation status.
Keywords: fungi; Holm oak; iberian peninsula; Mediterranean ecosystem; sporocarps

Rinodina evae (Physciaceae, Ascomycota), a new corticolous blastidiate species from Eastern Spain - Fos, Simón; Giralt, Mireia (Nova Hedwigia, 2009)
Rinodina evae, a new corticolous species, is described from Eastern Spain. It is mainly characterized by a blastidiate, hairy thallus, Pachysporaria-type ascospores and the lack of secondary lichen substances. Hitherto, it is only known from several cork-oak forests of Catalonia and the Valencian Community, where it always grows on virgin bark of Quercus suber. The new species is compared with Rinodina poeltiana, somewhat similar in habit, as well as with other corticolous blastidiate Rinodina species.
Keywords: Biodiversity; cork-oak forests; iberian peninsula; lichens; Rinodina; taxonomy

Rinodina evae (Physciaceae, Ascomycota), a new corticolous blastidiate species from Eastern Spain - Fos, Simón; Giralt, Mireia (Nova Hedwigia, 2009)
Rinodina evae, a new corticolous species, is described from Eastern Spain. It is mainly characterized by a blastidiate, hairy thallus, Pachysporaria-type ascospores and the lack of secondary lichen substances. Hitherto, it is only known from several cork-oak forests of Catalonia and the Valencian Community, where it always grows on virgin bark of Quercus suber. The new species is compared with Rinodina poeltiana, somewhat similar in habit, as well as with other corticolous blastidiate Rinodina species.
Keywords: Biodiversity; cork-oak forests; iberian peninsula; lichens; Rinodina; taxonomy

Assessing spider species richness and composition in Mediterranean cork oak forests - Cardoso, Pedro; Gaspar, Clara; Pereira, Luis C; Silva, Israel; Henriques, Sérgio S; da Silva, Ricardo R; Sousa, Pedro (Acta Oecologica, 2008)
Semi-quantitative sampling protocols have been proposed as the most cost-effective and comprehensive way of sampling spiders in many regions of the world. In the present study, a balanced sampling design with the same number of samples per day, time of day, collector and method, was used to assess the species richness and composition of a Quercus suber woodland in Central Portugal. A total of 475 samples, each corresponding to one hour of effective ﬁeldwork, were taken. One hundred sixty eight species were captured, of which 150 were recorded inside a delimited one-hectare plot; this number corresponds to around 90% of the estimated species richness. We tested the effect of applying different sampling approaches (sampling day, time of day, collector experience and method) on species richness, abundance, and composition. Most sampling approaches were found to inﬂuence the species measures, of which method, time of day and the respective interaction had the strongest inﬂuence. The data indicated that fauna depletion of the sampled area possibly occurred and that the inventory was reaching a plateau by the end of the sampling process. We advocate the use of the Chao estimators as best for intensive protocols limited in space and time and the use of the asymptotic properties of the Michaelis–Menten curve as a stopping or reliability rule, as it allows the investigator to know when a close-to-complete inventory has been obtained and when reliable non-parametric estimators have been achieved.
Keywords: araneae; Arrábida; Biodiversity assessment; iberian peninsula; methodology; Portugal; Quercus suber; Richness estimators; Semi-quantitative sampling; Stop-rules

Assessing spider species richness and composition in Mediterranean cork oak forests - Cardoso, Pedro; Gaspar, Clara; Pereira, Luis C.; Silva, Israel; Henriques, Sérgio S.; da Silva, Ricardo R.; Sousa, Pedro (Acta Oecologica, 2008)
Semi-quantitative sampling protocols have been proposed as the most cost-effective and comprehensive way of sampling spiders in many regions of the world. In the present study, a balanced sampling design with the same number of samples per day, time of day, collector and method, was used to assess the species richness and composition of a Quercus suber woodland in Central Portugal. A total of 475 samples, each corresponding to one hour of effective ﬁeldwork, were taken. One hundred sixty eight species were captured, of which 150 were recorded inside a delimited one-hectare plot; this number corresponds to around 90% of the estimated species richness. We tested the effect of applying different sampling approaches (sampling day, time of day, collector experience and method) on species richness, abundance, and composition. Most sampling approaches were found to inﬂuence the species measures, of which method, time of day and the respective interaction had the strongest inﬂuence. The data indicated that fauna depletion of the sampled area possibly occurred and that the inventory was reaching a plateau by the end of the sampling process. We advocate the use of the Chao estimators as best for intensive protocols limited in space and time and the use of the asymptotic properties of the Michaelis–Menten curve as a stopping or reliability rule, as it allows the investigator to know when a close-to-complete inventory has been obtained and when reliable non-parametric estimators have been achieved.
Keywords: araneae; Arrábida; Biodiversity assessment; iberian peninsula; methodology; Portugal; Quercus suber; Richness estimators; Semi-quantitative sampling; Stop-rules

Baseline characterization of major Iberian vegetation types based on the NDVI dynamics - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José (Plant Ecology, 2008)
We present an approach to derive baseline conditions for the radiation intercepted by vegetation in the largest remaining patches of homogeneous vegetation of the Iberian Peninsula. These baseline conditions can serve as a reference to assess environmental changes. We also characterized the major vegetation types of the Peninsula in the functional space deﬁned by the NDVI dynamics and analyzed the climatic controls of NDVI dynamics. We analysed the attributes of the NDVI seasonal dynamics: annual mean (NDVI-I), relative range (RREL), NDVI maximum and minimum values (MAX and MIN), months of MAX and MIN (MMAX and MMIN), and their inter-annual variabilities (1982–1999). We selected as reference sites only homogeneous pixels occupied by natural vegetation. We described their relationship with climatic variables using regression models. NDVI-I and RREL captured most of the variability of the NDVI annual proﬁle. Eurosiberian vegetation types were more productive, with winter minima and summer maxima. Mediterranean vegetation had summer minima and maxima distributed from autumn to spring. Interannual differences (higher in the Mediterranean) were low for NDVI-I and MAX and high for RREL and MIN. Precipitation was the main driver of NDVI-I for the Mediterranean pixels while temperature constrained it in the Eurosiberian ones. Seasonality (RREL) was associated with winter temperatures in Eurosiberian areas and with summer drought in Mediterranean ones. The Iberian vegetation types mainly differed in terms of total production and seasonality. Such differences were related to mean and inter-annual variation in precipitation and temperature associated with the Eurosiberian and Mediterranean climate zones. The NDVI dynamics allowed us to identify a functional signature for each vegetation type which captures differences that go beyond their range of climatic factors. Our baseline descriptions, based on a common approach to characterize vegetation functioning, are proposed as reference situations to evaluate the impact of environmental changes on the remaining large patches of single major natural and seminatural vegetation types.
Keywords: AVHRR/NOAA; ecosystem functioning; iberian peninsula; Normalized Difference Vegetation Index (NDVI); Regional analysis; Remote sensing

Baseline characterization of major Iberian vegetation types based on the NDVI dynamics - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José (Plant Ecology, 2008)
We present an approach to derive baseline conditions for the radiation intercepted by vegetation in the largest remaining patches of homogeneous vegetation of the Iberian Peninsula. These baseline conditions can serve as a reference to assess environmental changes. We also characterized the major vegetation types of the Peninsula in the functional space deﬁned by the NDVI dynamics and analyzed the climatic controls of NDVI dynamics. We analysed the attributes of the NDVI seasonal dynamics: annual mean (NDVI-I), relative range (RREL), NDVI maximum and minimum values (MAX and MIN), months of MAX and MIN (MMAX and MMIN), and their inter-annual variabilities (1982–1999). We selected as reference sites only homogeneous pixels occupied by natural vegetation. We described their relationship with climatic variables using regression models. NDVI-I and RREL captured most of the variability of the NDVI annual proﬁle. Eurosiberian vegetation types were more productive, with winter minima and summer maxima. Mediterranean vegetation had summer minima and maxima distributed from autumn to spring. Interannual differences (higher in the Mediterranean) were low for NDVI-I and MAX and high for RREL and MIN. Precipitation was the main driver of NDVI-I for the Mediterranean pixels while temperature constrained it in the Eurosiberian ones. Seasonality (RREL) was associated with winter temperatures in Eurosiberian areas and with summer drought in Mediterranean ones. The Iberian vegetation types mainly differed in terms of total production and seasonality. Such differences were related to mean and inter-annual variation in precipitation and temperature associated with the Eurosiberian and Mediterranean climate zones. The NDVI dynamics allowed us to identify a functional signature for each vegetation type which captures differences that go beyond their range of climatic factors. Our baseline descriptions, based on a common approach to characterize vegetation functioning, are proposed as reference situations to evaluate the impact of environmental changes on the remaining large patches of single major natural and seminatural vegetation types.
Keywords: AVHRR/NOAA; ecosystem functioning; iberian peninsula; Normalized Difference Vegetation Index (NDVI); Regional analysis; Remote sensing

Effects of climate change on the distribution of Iberian tree species - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Applied Vegetation Science, 2008)
Question: Will the predicted climate changes affect species distribution in the Iberian Peninsula? Location: Iberian Peninsula (Spain and Portugal). Methods: We modelled current and future tree distributions as a function of climate, using a computational framework that made use of one machine learning technique, the random forest (RF) algorithm. This algorithm provided good predictions of the current distribution of each species, as shown by the area under the corresponding receiver operating characteristics (ROC) curves. Species turnover, richness and the change in distributions over time to 2080 under four Intergovernmental panel on climate change (IPCC) scenarios were calculated using the species map outputs. Results and Conclusions: The results show a notable reduction in the potential distribution of the studied species under all the IPCC scenarios, particularly so for mountain conifer species such as Pinus sylvestris, P. uncinata and Abies alba. Temperate species, especially Fagus sylvatica and Quercus petraea, were also predicted to suffer a reduction in their range; also sub-mediterranean species, especially Q. pyrenaica, were predicted to undergo notable decline. In contrast, typically Mediterranean species appeared to be generally more capable of migration, and are therefore likely to be less affected.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 1990; 2002; amaral franco; avishai; for quercus pubescens; Forest distributions; govaerts; iberian peninsula; learning; machine; Machine learning; nomenclature; random forest

Effects of climate change on the distribution of Iberian tree species - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Applied Vegetation Science, 2008)
Question: Will the predicted climate changes affect species distribution in the Iberian Peninsula? Location: Iberian Peninsula (Spain and Portugal). Methods: We modelled current and future tree distributions as a function of climate, using a computational framework that made use of one machine learning technique, the random forest (RF) algorithm. This algorithm provided good predictions of the current distribution of each species, as shown by the area under the corresponding receiver operating characteristics (ROC) curves. Species turnover, richness and the change in distributions over time to 2080 under four Intergovernmental panel on climate change (IPCC) scenarios were calculated using the species map outputs. Results and Conclusions: The results show a notable reduction in the potential distribution of the studied species under all the IPCC scenarios, particularly so for mountain conifer species such as Pinus sylvestris, P. uncinata and Abies alba. Temperate species, especially Fagus sylvatica and Quercus petraea, were also predicted to suffer a reduction in their range; also sub-mediterranean species, especially Q. pyrenaica, were predicted to undergo notable decline. In contrast, typically Mediterranean species appeared to be generally more capable of migration, and are therefore likely to be less affected.
Keywords: 1990; 2002; amaral franco; avishai; for quercus pubescens; Forest distributions; govaerts; iberian peninsula; learning; machine; Machine learning; nomenclature; random forest

Mitochondrial markers reveal deep population subdivision in the European protected spider Macrothele calpeiana (Walckenaer, 1805) (Araneae, Hexathelidae) - Arnedo, Miquel A; Ferrandez, Miguel-Angel (CONSERVATION GENETICS, 2007)
The funnel-web spider genus Macrothele is the only representative of the mygalomorph family Hexathelidae not found in Australia or New Zealand. Its 26 species occur in Central Africa and the Oriental region. Two Macrothele species are found in Europe: M. cretica Kulczynski, 1903 from Crete, and M. calpeiana (Walckenaer, 1805) type species of the genus and the largest European spider, whose distribution extends across the south-eastern Iberian Peninsula, and in two localities of North Africa. Macrothele calpeiana is the only spider protected under European legislation. The fragmentation and destruction of the cork oak forest, with which M. calpeiana was thought to be closely associated, prompted the inclusion of this species in the Bern Convention. Some authors, however, have challenged this view and consider M. calpeiana to be neither a cork oak forest bioindicator nor an endangered species. By contrast, other observations suggest that the distribution of the species is extremely fragmented and that most local populations should be considered as threatened. In this paper, we examine aspects of the conservation status of M. calpeiana in the light of molecular phylogenetic analyses based on mitochondrial markers of sample specimens from major populations. Our data confirm the fragmented distribution of M. calpeiana and reveal high levels of genetic differentiation across its populations. Local population growth cannot be ruled out, though the lineage as a whole has apparently not undergone population growth. Lineage age estimates suggest that M. calpeiana colonized the Iberian Peninsula during the Messinian salinity crisis and that the current population fragmentation originates from the Pliocene and Pleistocene. We argue that the fragmentation and deep genetic divergence across populations, along with evolutionary singularity and endemicity in one of Europe's main biodiversity hotspots, support the preservation of its legally protected status.
Keywords: Betic-Rifean region; iberian peninsula; mitochondrial genetic variation; population fragmentation; spider conservation

Mitochondrial markers reveal deep population subdivision in the European protected spider Macrothele calpeiana (Walckenaer, 1805) (Araneae, Hexathelidae) - Arnedo, Miquel A.; Ferrandez, Miguel-Angel (CONSERVATION GENETICS, 2007)
The funnel-web spider genus Macrothele is the only representative of the mygalomorph family Hexathelidae not found in Australia or New Zealand. Its 26 species occur in Central Africa and the Oriental region. Two Macrothele species are found in Europe: M. cretica Kulczynski, 1903 from Crete, and M. calpeiana (Walckenaer, 1805) type species of the genus and the largest European spider, whose distribution extends across the south-eastern Iberian Peninsula, and in two localities of North Africa. Macrothele calpeiana is the only spider protected under European legislation. The fragmentation and destruction of the cork oak forest, with which M. calpeiana was thought to be closely associated, prompted the inclusion of this species in the Bern Convention. Some authors, however, have challenged this view and consider M. calpeiana to be neither a cork oak forest bioindicator nor an endangered species. By contrast, other observations suggest that the distribution of the species is extremely fragmented and that most local populations should be considered as threatened. In this paper, we examine aspects of the conservation status of M. calpeiana in the light of molecular phylogenetic analyses based on mitochondrial markers of sample specimens from major populations. Our data confirm the fragmented distribution of M. calpeiana and reveal high levels of genetic differentiation across its populations. Local population growth cannot be ruled out, though the lineage as a whole has apparently not undergone population growth. Lineage age estimates suggest that M. calpeiana colonized the Iberian Peninsula during the Messinian salinity crisis and that the current population fragmentation originates from the Pliocene and Pleistocene. We argue that the fragmentation and deep genetic divergence across populations, along with evolutionary singularity and endemicity in one of Europe's main biodiversity hotspots, support the preservation of its legally protected status.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Betic-Rifean region; iberian peninsula; mitochondrial genetic variation; population fragmentation; spider conservation

Molecular and palaeoecological evidence for multiple glacial refugia for evergreen oaks on the Iberian Peninsula - López de Heredia, U.; Carrión, J. S.; JIMÉNEZ, P.; COLLADA, C.; Gil, L. (Journal of Biogeography, 2007)
Aim A multiple glacial refugia hypothesis for Mediterranean plant species was tested with the evergreen Quercus complex (Quercus suber L., Quercus ilex L. and Quercus coccifera L.) from the Iberian Peninsula, using molecular and palaeobotanical data. Location The Iberian Peninsula, which is an ecologically and physiographically complex area located on the western edge of the Mediterranean Basin. Methods We sampled 1522 individuals from 164 populations of Q. suber, Q. ilex and Q. coccifera. A review of the recent literature on fossil pollen and charcoal records and a nested clade analysis on chloroplast DNA polymerase chain reaction-restriction fragment length polymorphism was carried out to infer demographic and historical processes. Results The analysis indicates at least one glacial refugium for Q. suber in southwestern Iberia. Extensive introgression of Q. suber with Q. ilex indicates several potential refugia in eastern Iberia. Past fragmentation was followed by a restricted range ﬂow/range expansion, suggesting multiple refugia for Q. ilex–Q. coccifera elsewhere in central and northern Iberia and multiple areas of secondary contact. This ﬁnding is consistent with fossil records. Main conclusions The predicted multiple refugia during glacial periods indicates the existence of secondary post-glaciation contact areas. These areas contained complex diversity patterns resulting mainly from range expansions followed by isolation by distance. To a lesser degree, traces of restricted and longdistance dispersal were also found.
Keywords: cpDNA PCR-RFLPs; evergreen Quercus; fossil pollen; glacial refugia; iberian peninsula; introgression; nested clade analysis; oaks; phylogeography

Predictive modelling of tree species distributions on the Iberian Peninsula during the Last Glacial Maximum and Mid-Holocene - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Ecography, 2007)
This paper reports a bioclimatic envelope model study of the potential distribution of 19 tree species in the Iberian Peninsula during the Last Glacial Maximum (LGM; 21 000 yr BP) and the Mid-Holocene (6000 yr BP). Current patterns of tree species richness and distributions are believed to have been strongly influenced by the climate during these periods. The modelling employed novel machine learning techniques, and its accuracy was evaluated using a threshold-independent method. Two atmospheric general circulation models, UGAMP and ECHAM3 (generated by the Palaeoclimate Modelling Intercomparison Project, PMIP), were used to provide climate scenarios under which the distributions of the 19 tree species were modelled. The results obtained for these scenarios were assessed by agreement measure analysis; they differed significantly for the LGM, but were more similar for the Mid-Holocene. The results for the LGM support the inferred importance of pines in the Iberian Peninsula at this time, and the presence of evergreen Quercus in the south. Important differences in the altitude at which the modelled species grew were also predicted. During the LGM, some normally higher mountain species potentially became re-established in the foothills of the Pyrenees. The warm Mid-Holocene climate is clearly reflected in the predicted expansion of broad-leaved forests during this period, including the colonization of the northern part of the Iberian Peninsula by evergreen Quercus species.
Keywords: climate scenarios; iberian peninsula; Pinus; Quercus; refugia (voyant); species distribution modelling

Predictive modelling of tree species distributions on the Iberian Peninsula during the Last Glacial Maximum and Mid-Holocene - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Ecography, 2007)
This paper reports a bioclimatic envelope model study of the potential distribution of 19 tree species in the Iberian Peninsula during the Last Glacial Maximum (LGM; 21 000 yr BP) and the Mid-Holocene (6000 yr BP). Current patterns of tree species richness and distributions are believed to have been strongly influenced by the climate during these periods. The modelling employed novel machine learning techniques, and its accuracy was evaluated using a threshold-independent method. Two atmospheric general circulation models, UGAMP and ECHAM3 (generated by the Palaeoclimate Modelling Intercomparison Project, PMIP), were used to provide climate scenarios under which the distributions of the 19 tree species were modelled. The results obtained for these scenarios were assessed by agreement measure analysis; they differed significantly for the LGM, but were more similar for the Mid-Holocene. The results for the LGM support the inferred importance of pines in the Iberian Peninsula at this time, and the presence of evergreen Quercus in the south. Important differences in the altitude at which the modelled species grew were also predicted. During the LGM, some normally higher mountain species potentially became re-established in the foothills of the Pyrenees. The warm Mid-Holocene climate is clearly reflected in the predicted expansion of broad-leaved forests during this period, including the colonization of the northern part of the Iberian Peninsula by evergreen Quercus species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate scenarios; iberian peninsula; Pinus; Quercus; refugia (voyant); species distribution modelling

Litter production in a Quercus suber forest of Montseny (NE Spain) and its relationship to meteorological conditions - Caritat, Antònia; García-Berthou, Emili; Lapeña, Roger; Vilar, Lluís (Ann. For. Sci., 2006)
From 1996 to 2002 the monthly litterfall in a Quercus suber forest ecosystem of Montseny (NE Spain) was recorded and its relationship to meteorological variables was statistically analysed. The average annual production (477 g m-2 yr-1) was similar to those found in other Mediterranean evergreen forests with relatively high rainfall. The main components were the leaves (55% of the total biomass), followed by acorns (22%) and twigs (16%). Litter production was highest during May and June, when the majority of the old leaves fell. When the meteorological conditions were favourable, a second leaf fall collection was observed. Acorn production in 2001 was about nine times that of the previous years, indicating a mast year. In general, the different litterfall components were highly correlated in time except for the acorns. Interannual covariation was significant for leaves/twigs and leaves/catkins. Catkins were the most variable component with also strong seasonality, acorns were also very variable with low seasonality, while leaves were less variable and with the strongest seasonality. After accounting for seasonal covariation, there were significant effects of rainfall on twig litterfall and of temperature on leaf litterfall, the years with highest leaf litterfall being the hottest.
Keywords: coark oak; iberian peninsula; litterfall; Mediterranean climate; Weather

Litter production in a Quercus suber forest of Montseny (NE Spain) and its relationship to meteorological conditions - Caritat, Antònia; García-Berthou, Emili; Lapeña, Roger; Vilar, Lluís (Ann. For. Sci., 2006)
From 1996 to 2002 the monthly litterfall in a Quercus suber forest ecosystem of Montseny (NE Spain) was recorded and its relationship to meteorological variables was statistically analysed. The average annual production (477 g m-2 yr-1) was similar to those found in other Mediterranean evergreen forests with relatively high rainfall. The main components were the leaves (55% of the total biomass), followed by acorns (22%) and twigs (16%). Litter production was highest during May and June, when the majority of the old leaves fell. When the meteorological conditions were favourable, a second leaf fall collection was observed. Acorn production in 2001 was about nine times that of the previous years, indicating a mast year. In general, the different litterfall components were highly correlated in time except for the acorns. Interannual covariation was significant for leaves/twigs and leaves/catkins. Catkins were the most variable component with also strong seasonality, acorns were also very variable with low seasonality, while leaves were less variable and with the strongest seasonality. After accounting for seasonal covariation, there were significant effects of rainfall on twig litterfall and of temperature on leaf litterfall, the years with highest leaf litterfall being the hottest.
Keywords: coark oak; iberian peninsula; litterfall; Mediterranean climate; Weather

Biennial acorn maturation and its relationship with flowering phenology in Iberian populations of Quercus suber - Díaz-Fernández, Pedro M.; Climent, José; Gil, Luis (Trees, 2004)
Since the XIX century, there is a controversy about the existence of biennial maturation of the acorns in Quercus suber L. While some authors recognised biennial cycles as an adaptation to habitats with short vegetative periods, other authors discarded the biennial pattern. Successive flowering events from spring to autumn and annual acorn ripening are proposed as an explanation of the multiple acorn crops typical of Iberian forests. To clarify this discussion, the presence of annual and biennial acorns was assessed in seven cork oak stands, covering a wide range of environmental conditions. In each stand, 100 individuals were sampled once in spring and once in autumn. Biennial acorns were observed with variable frequencies in all populations. There was a significant and positive relationship between latitude and the percentage of trees with biennial acorns within northern and central populations. On the contrary, this trend was not significant among southern populations. The hypothesis that the presence of biennial acorns in Quercus suber is related to individual female flowering phenology was confirmed in four populations located in the southwestern Iberian Peninsula. Unregarding local differences in the distribution of phenological stages anticipated trees bore significantly less biennial acorns than delayed individuals of the same stand. This result is coherent with the idea that the length of the vegetative period plays a crucial role in the frequency of annual and biennial acorn ripening patterns. The relationship between annual and biennial ripening cycles and the multiple acorn crops is discussed
Keywords: Cork oak; iberian peninsula; Phenology; quiescent flowers; ripening cycle

Biennial acorn maturation and its relationship with flowering phenology in Iberian populations of Quercus suber - Díaz-Fernández, Pedro M; Climent, José; Gil, Luis (Trees, 2004)
Since the XIX century, there is a controversy about the existence of biennial maturation of the acorns in Quercus suber L. While some authors recognised biennial cycles as an adaptation to habitats with short vegetative periods, other authors discarded the biennial pattern. Successive flowering events from spring to autumn and annual acorn ripening are proposed as an explanation of the multiple acorn crops typical of Iberian forests. To clarify this discussion, the presence of annual and biennial acorns was assessed in seven cork oak stands, covering a wide range of environmental conditions. In each stand, 100 individuals were sampled once in spring and once in autumn. Biennial acorns were observed with variable frequencies in all populations. There was a significant and positive relationship between latitude and the percentage of trees with biennial acorns within northern and central populations. On the contrary, this trend was not significant among southern populations. The hypothesis that the presence of biennial acorns in Quercus suber is related to individual female flowering phenology was confirmed in four populations located in the southwestern Iberian Peninsula. Unregarding local differences in the distribution of phenological stages anticipated trees bore significantly less biennial acorns than delayed individuals of the same stand. This result is coherent with the idea that the length of the vegetative period plays a crucial role in the frequency of annual and biennial acorn ripening patterns. The relationship between annual and biennial ripening cycles and the multiple acorn crops is discussed
Keywords: Cork oak; iberian peninsula; Phenology; quiescent flowers; ripening cycle

Patch occupancy by stone martens Martes foina in fragmented landscapes of central Spain: the role of fragment size, isolation and habitat structure - Virgós, Emilio; García, Francisco J (Acta Oecologica, 2002)
We studied the response to forest fragmentation of a generalist carnivore, the stone marten Martes foina, in highly fragmented landscapes of central Spain. Five different areas (n = 178 fragments) in central Spain were surveyed. This paper analyses the relationship between fragment use by martens (measured through scat presence) and a series of variables related to the size, isolation and vegetation structure of each fragment by means of stepwise logistic regression. Size and isolation have an important effect on stone marten presence in fragments. Our results were similar to those found for other marten species in landscapes with coarse-grain fragmentation, but they contrast with other studies conducted in landscapes with ﬁne-grain fragmentation. These data suggested that in highly fragmented landscapes, size and isolation factors resulting from forest fragmentation were responsible for determining marten responses, irrespective of their habitat generalism. Management policies for the stone marten in highly fragmented scenarios require the maintenance of large forests near continuous forest tracts in mountains or riparian woodlands
Keywords: agricultural landscapes; Forest fragmentation; iberian peninsula; martes foina; size-isolation effects

Patch occupancy by stone martens Martes foina in fragmented landscapes of central Spain: the role of fragment size, isolation and habitat structure - Virgós, Emilio; García, Francisco J. (Acta Oecologica, 2002)
We studied the response to forest fragmentation of a generalist carnivore, the stone marten Martes foina, in highly fragmented landscapes of central Spain. Five different areas (n = 178 fragments) in central Spain were surveyed. This paper analyses the relationship between fragment use by martens (measured through scat presence) and a series of variables related to the size, isolation and vegetation structure of each fragment by means of stepwise logistic regression. Size and isolation have an important effect on stone marten presence in fragments. Our results were similar to those found for other marten species in landscapes with coarse-grain fragmentation, but they contrast with other studies conducted in landscapes with ﬁne-grain fragmentation. These data suggested that in highly fragmented landscapes, size and isolation factors resulting from forest fragmentation were responsible for determining marten responses, irrespective of their habitat generalism. Management policies for the stone marten in highly fragmented scenarios require the maintenance of large forests near continuous forest tracts in mountains or riparian woodlands
Keywords: agricultural landscapes; Forest fragmentation; iberian peninsula; martes foina; size-isolation effects

Past distribution and ecology of the cork oak (Quercus suber) in the Iberian Peninsula: a pollen-analytical approach - Carrión, J. S.; Parra, I.; Navarro, C.; Munuera, M. (Diversity and Distributions, 2000)
This study presents pollen-analytical data from continental and offshore Iberian Peninsula sites that include pollen curves of Quercus suber, to provide information on the past distribution and ecology of the cork oak (Q. suber). Results centre on a new pollen record of Navarrés (Valencia, eastern Spain), which shows that the cork oak survived regionally during the Upper Pleistocene and was important during a mid-Holocene replacement of a local pine forest by Quercus-dominated communities. This phenomenon appears linked to the recurrence of ﬁre and reinforces the value of the cork oak for reforestation programmes in ﬁre-prone areas. In addition to Navarrés, other Late Quaternary pollen sequences (Sobrestany, CasablancaAlmenara, Padul, SU 8103, SU8113, 8057B) suggest last glacial survival of the cork oak in southern and coastal areas of the Peninsula and North Africa. Important developments also occur from the Late Glacial to the middle Holocene, not only in the west but also in the eastern Peninsula. It is suggested that, in the absence of human inﬂuence, Q. suber would develop in non-monospeciﬁc forests, sharing the arboreal stratum both with other sclerophyllous and deciduous Quercus and Pinus species
Keywords: Cork oak; historical biogeography; iberian peninsula; palaeoecology; pollen.

Past distribution and ecology of the cork oak (Quercus suber) in the Iberian Peninsula: a pollen-analytical approach - Carrión, J S; Parra, I; Navarro, C; Munuera, M (Diversity and Distributions, 2000)
This study presents pollen-analytical data from continental and offshore Iberian Peninsula sites that include pollen curves of Quercus suber, to provide information on the past distribution and ecology of the cork oak (Q. suber). Results centre on a new pollen record of Navarrés (Valencia, eastern Spain), which shows that the cork oak survived regionally during the Upper Pleistocene and was important during a mid-Holocene replacement of a local pine forest by Quercus-dominated communities. This phenomenon appears linked to the recurrence of ﬁre and reinforces the value of the cork oak for reforestation programmes in ﬁre-prone areas. In addition to Navarrés, other Late Quaternary pollen sequences (Sobrestany, CasablancaAlmenara, Padul, SU 8103, SU8113, 8057B) suggest last glacial survival of the cork oak in southern and coastal areas of the Peninsula and North Africa. Important developments also occur from the Late Glacial to the middle Holocene, not only in the west but also in the eastern Peninsula. It is suggested that, in the absence of human inﬂuence, Q. suber would develop in non-monospeciﬁc forests, sharing the arboreal stratum both with other sclerophyllous and deciduous Quercus and Pinus species
Keywords: Cork oak; historical biogeography; iberian peninsula; palaeoecology; pollen.

Breeding performance of the Blue Tit Parus caeruleus in a patchy Mediterranean landscape - Catalan, R M; Haeger, J F (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1999)
This study compares reproductive strategy and breeding success of Parus caeruleus in a helm-oak (Quercus rotundifolia) forest and a pine plantation (Pinus pinea and P. pinaster) in the southern Iberian Peninsula. During the breeding period, an asymmetric flow of individuals takes place from the helm-oak forest to the pine plantation. This flow is favoured by nestboxes where Blue tits can lay their eggs. During the winter, a large part of the population moves back from the pine plantation to the helm-oak forest. Breeding pair density was much higher in the helm-oak forest than in the pine plantation. This may bt accounted for by the poorer quality of the resources available in the pine plantation which birds try to compensate for with larger breeding territories. Breeding density and most life-history traits examined (timing of breeding, clutch site, egg size, number of fledglings and fledgling weight) were similar in both habitats, as a result of the phenotypic plasticity of this species. Although breeding success was similar in both habitats, recruitment of new individuals per unit area was higher in the helm-oak forest. The consequences of pine plantations, as a form of forestry management, on species conservation is discussed.
APS
Keywords: breeding success; Holm oak; iberian peninsula; Parus caeruleus; Pinus pinaster; Pinus pinea; Quercus ilex; reproductive strategies

Dehesa ecosystem: Production and preservation - Olea, L; Figuera, F (Options Méditerranéennes, 1999)
The Dehesa is an ecosystem in which species of herbs, bushes and trees coexist in a semi-desert regime, contributingto the feeding of domestic and wild animals. The improvement and exploitation of these agrosylvopastoral systems must be founded on the principles of preseofr vthaetio ne nvironment and the idea of creating systems that can be maintained with a correct usage of natural resources. Fertilization of the natural pastures, the introduction of new pasture species and varieties, the favouring of the species of bush that have a forage value and the preservationo f the arboreous stratum are methods which will alluosw t o preserve this ecosystem
Keywords: Dehesa; forages; iberian peninsula; pastures

Sclerophyllous vegetation dynamics in the north of the Iberian peninsula during the last 16,000 years - RAMIL-REGO, P; RODRÍGUEZ-GUITIÁN, M; MUÑOZ-SOBRINO, C (Global Ecology and Biogeography, 1998)
We used pollen analysis to evaluate the dynamics of sclerophyllous arboreal taxa during the last 16,000 years. Quercus ilex type pollen and, to a lesser degree, other sclerophyllous elements (e.g. Olea and Phillyrea) have been documented during the Late-glacial in the majority of the sequences obtained in continental territories in the north of the Iberian peninsula, as well as in the eastern coastal/sub-coastal area in the Cantabric region. During the Late-glacial and the Holocene, sclerophyllous elements became widespread in many areas of the north Iberian peninsula (the Sil, Duero and Ebro depressions and the southernmost slopes of adjacent mountains), with the smallest pollinic representation of these taxa being for the most septentrional areas (coastal/sub-coastal territories and the northermost slopes of the Cantabrian-Atlantic Mountains). During these periods, there is no indication of the presence of Quercus ilex pollen in the northwestern territories, which would explain the absence of this species in the present-day landscape. Despite the widespread distribution that sclerophyllous elements have maintained during the last 16,000 years, they have never attained a predominant role in the landscape, having a smaller representation, both during hotter and colder phases, than deciduous forests, pine forests and mixed forests.
Keywords: Holocene; iberian peninsula; Late-glacial; palynology; Quercus ilex; sclerophyllous forests; species range; vegetation history